Edukasi Literasi Kesehatan Reproduksi Bagi Orang Muda Katolik dan Ibu Sebagai Pendamping - Inderawati, Maria Magdalena Wahyuni; Sukwadi, Ronald; Silalahi, Agustinus; Silitonga, Riana Magdalena; Sari, Indah Munica; Santoso, Hieronimus Barakhiel Arza; Candra, Sofia (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2026)
Rapid exposure to digital media and information has contributed to limited and sometimes inaccurate understanding of human life, anatomy, and reproductive health among Catholic youth and mother. This condition highlights the need for educational approaches that integrate scientific knowledge with faith-based values. This community engagement program aimed to enhance life and reproductive health literacy among Catholic youth and mothers through experiential learning. The activity was conducted through an educational visit to the Anatomy Museum of the Faculty of Medicine and Health Sciences, Atma Jaya Catholic University of Indonesia. Participants observed anatomical collections, including human organs and fetal development models, guided by museum educators. Interactive explanations, group discussions, and a structured question-and-answer session were provided to encourage reflection and understanding. Participant responses and learning outcomes were evaluated using post-activity questionnaires. The results indicate a significant increase in participants’ understanding of human anatomy and the value of human life. Most participants expressed high satisfaction with the activity and reported that visual, hands-on learning made complex and sensitive topics easier to comprehend. The fetal development section was recognized as the most influential in promoting contemplation of the dignity of life. In conclusion, anatomy museum–based experiential education is an effective approach to improving life and reproductive health literacy while supporting values-based learning.